Moral educational milestones in the thought of Mrs. Zahraa - A Quranic Interpretive Approach – (Journal of the College of Basic Education, 2024)
Lady Fatima Al-Zahra has a high position in Islamic thought, and her Fadak sermon contains deep Islamic knowledge.The research consisted of an introduction and preface to the sources of moral education in Islam and demands about the moral educational landmarks that were in: the etiquette of greetings, the morals of hypocrisy, the morals of gentleness, and the morals of firmness, and through an interpretive Qur’anic study so that the goal would become clearer through the opinions of the commentators in explaining the Qur’anic verses, followed by a conclusion and a list of sources.